Occupational Self-Perception Level Effects on the Development of Kinesiophobia in Individuals With Total Knee Arthroplasty - Yılmaz, Güleser Güney; AKEL, BURCU SEMİN; SAİTOĞLU, YELİZ SEVİMLİ; Akı, Esra (Elsevier, 2023)
Introduction: The development of kinesiophobia after Total Knee Arthroplasty (TKA) has been one of the important issues. However, the early results and the presence of kinesiophobia before surgery have not been adequately investigated. In addition, the effects of factors such as pain perception, postoperative pain level, and demographic characteristics were mentioned. However, occupational factors such as occupational expectations and occupational self-perception level have not been adequately investigated.Methods: Each assessment tool was administered three times: once on the first day of the preoperative period and then again at the third and sixth weeks after the surgery. The assessment tools employed were the Knee Injury and Osteoarthritis Outcome Score, Tampa Scale for Kinesiophobia, Occupational Self Assessment, and Timed Up and Go test. To analyze the differences in Tampa Scale for Kinesiophobia scores, a one-way ANOVA was con-ducted. Subsequently, the patients were categorized into two groups based on their level of kinesiophobia: high and low. Independent sample t-tests were employed to compare continuous and normally distributed data be-tween the two groups, while the Mann-Whitney U test was used for non-normally distributed data. The Pearson correlation coefficient was utilized to assess the relationship between continuous data, whereas the Spearman rank-order correlation was employed for non-normally distributed data. Results: High levels of kinesiophobia were identified in individuals both prior to and following surgery. Signif-icant differences were observed between the high and low kinesiophobia groups in terms of the mean OSA Competency (p < 0.05). However, no statistically significant differences were found between the groups in relation to the other evaluation scores during the follow-up periods. Furthermore, a negative correlation was observed between TSK score and OSA Competence results (p < 0.05).Conclusion: Occupational self-perception levels effect the level of kinesiophobia in individuals with TKA and high rates of kinesiophobia observed before the surgery intensified after the surgery, especially in the early period. It may be necessary to focus more on factors such as individual factors, individuals' values, habits, and beliefs.
Keywords: Total Knee Arthroplasty; Kinesiophobia; Occupational Self-Perception